2015
DOI: 10.1001/jamadermatol.2014.3889
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Mobile Application Delivering Personalized, Real-Time Sun Protection Advice

Abstract: Importance Mobile smart phones are rapidly emerging as an effective means of communicating with many Americans. Using mobile applications, they can access remote databases, track time and location, and integrate user input to provide tailored health information. Objective A smart phone mobile application providing personalized, real-time sun protection advice was evaluated in a randomized trial. Design The trial was conducted in 2012 and had a randomized pretest-posttest controlled design with a 10-week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 38 publications
(39 reference statements)
1
80
0
2
Order By: Relevance
“…Buller et al have published their work [18,19,20] reporting on the development of the app Solar Cell, designed for the Android smartphone, and where the aim is to provide real time sun protection advice. The pilot stage included the running of focus groups for conceptual determination [18], followed by four rounds of usability testing to develop the app interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buller et al have published their work [18,19,20] reporting on the development of the app Solar Cell, designed for the Android smartphone, and where the aim is to provide real time sun protection advice. The pilot stage included the running of focus groups for conceptual determination [18], followed by four rounds of usability testing to develop the app interface.…”
Section: Discussionmentioning
confidence: 99%
“…This work found that adults desired sun protection advice, they identified few barriers to app use and were willing to input personal data. Further research [19] included a randomised controlled trial pre-test post-test design with 10 week follow up for usability testing and to assess if the system was interoperable across handsets and networks. The system was found to be highly user friendly with a mean of 5.06 (Range 0 = worst imaginable to 7 = best imaginable) [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous examples of app based (automated) informed consent procedures in mHealth research [11,12]. In several studies, electronic signatures were identified as sufficient to validate the consent process [13,14]. Women in the Dot study had three choices: 1) completing the informed consent through a fully automated process, 2) having a phone call with study representatives, or 3) utilizing chat functionality.…”
Section: Modification 3: Self-enroll Mechanism (Recruitment Weeks 16-26)mentioning
confidence: 99%
“…Advanced technology has provided a more efficient method in which to conduct certain aspects of preventive trials and clinical trials (21). It has enhanced recruitment of patients and has been able overcome limitations of existing methods through which trials are run and patients are recruited (22,23). Caution is needed, however, when ultra-modern technologies are introduced in the setting of clinical trials to ensure key aspects such as consent are conducted in an appropriate manner (24).…”
Section: Advanced Technology In Cancer Prevention and Controlmentioning
confidence: 99%